Risk preference and willingness to participate in the futures market: Evidence from cotton and jujube enterprises of China - Cheng, An; Han, Xinru; Ahmad, Mahmood (Frontiers in Environmental Science, 2022)
Since the instability and uncertainty are mounting on the international landscape, it is urgent and necessary to explore the risk awareness and risk management capabilities of leading agricultural enterprises in China. Based on a survey of 219 enterprises, we build a logit model and estimate the impact of risk preference and price risk perception of leading cotton and jujube enterprises on their willingness to participate in the futures market. We further explore the moderating effect of the price risk perception on the relationship between risk preference and willingness to participate in the futures market. Results show that the risk preference and price risk perception of leading enterprises have a significant positive impact on their willingness to participate in the futures market, and the proportion of the mediating effect in the total effect is calculated to be 35.1%. Therefore, risk management instruments suitable for various types of leading enterprises and segmentation of training courses are suggested to optimize the effectiveness of China’s cotton and jujube futures market.